Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan - Mita, Toshiharu; Nagano, Hiroshi; Olmi, Massimo (Zootaxa, 2017)
The fauna of Dryinidae and Embolemidae from Anijima in Ogasawara Islands, Japan is surveyed. Five species of Dryinidae and one of Embolemidae. Gonatopus adelphos Mita & Olmi, sp. nov. and Ampulicomorpha viator Mita & Olmi, sp. nov. are described and illustrated. Gonatopus tambiniae (Esaki & Hashimoto) is recorded for the first time from Anijima. Anteon achterbergi Olmi, Gonatopus nigricans (R. Perkins) are recorded for the first time from Ogasawara Islands. The male of Dryinus sinicus Olmi is described for the first time. Gonatopus hagoromo Terayama & Ohbayashi is considered junior synonymous of Gonatopus tambiniae (Esaki & Hashimoto).